G129 'When things get on top of me....'A retrospective study of deliberate self - harm in children aged below 14 years. (7th April 2014) - Rao, V; Dave, A
Abstract : Introduction: Deliberate self harm (DSH) is a major public health issue affecting 1 in 15 young people in the UK. Madge et al (2008) reported that over 70% of 15–16 year-olds admitted to self-harming at some stage in their lives. There is very little information on DSH in children aged below 14 years. Aim: To study the basic epidemiology of DSH in children aged under 14 years. Method: Children under 14 who were admitted to hospital for DSH over a 2 year period were included. Data was collected from clinical records of the Child and Adolescent Mental Health Service (CAMHS) Results: Of the district's child population of 70, 000, 186 children under 17 years of age (41 boys and 145 girls) were admitted with DSH. 18 (10.5%) of these were under 14 (11 boys and 7 girls). The results apply to this group. Age distribution Image 1 15 White British ; 4 looked after. In 4 children there had been a previous admission for DSH, and in one child there had been 2 previous attempts in the same 2-year period. A further 10 children reported attempts at DSH prior to this period. There was a family history of depression in 3 cases, schizophrenia in 1, one attempted suicide in 1 case and a completed suicide in 1 case. 4 children had autism spectrum disorder, one had ADHD and 1 had cerebral palsy 6 were already under CAMHS . Reasons for DSH – Image 2 Methodof DSH – Image 3 Summary: 10% of children who self harmed were under 14, bullying, school difficulties, family problems were the common reasons for DSH overdose was the commonest method; many threatened to self harm with a knife or attempted self strangulation. most children had tried DSH in the past and 5 in the last 2 years. a third had neurodisability, a third had a family history of mental illness. Conclusions: It is of great concern that some children as young as 8 and 9 self harm. There are no universal screening tests to assess risk of DSH in children. Professionals working with children and adults need to adopt a 'whole-family' approach even if either present initially to services. Schools need to have and adhere to robust anti-bullying policies.